Influence of collaborative learning on the ddevelopment of writing slills with solidiers from the first year candidates course, classroom I at Esforse during the first semester 2015 - Cunalata Chango, Miguel Edmundo (2015)
This research project is based on an analysis of test scores from previous levels of English language soldier candidates attending ESFORSE, whereby poor performance especially in the writing skills was established. In order to solve this issue, a problem tree was designed for identification of causes and effects that in turn resulted in the setting of the independent (Collaborative Learning) and dependent (Writing skill) variables. Afterwards, a variables matrix was defined to establish the relationship between both variables and then the general and specific objectives of this research were set up; in this sense, the Theoretical Framework describes on Collaborative Learning and writing skills in detail. At the end of this element, the hypotheses were formulated. This research used a descriptive, of field and quasi-experimental design; at the beginning of this study, a pre-test was applied to two groups; the experimental group comprised 32 candidates, and the control group comprised also 32, they were evaluated on writing skills in a real situation before the application of the Collaborative Learning Approach.